Parental reporting of smelly urine and urinary tract infection. Issue 3 (1st March 2003) - Struthers, S; Scanlon, J; Parker, K; Goddard, J; Hallett, R
Abstract : Background: Parents often report that young children have "smelly urine" or a particular urinary odour. There is little evidence that these observations are relevant to the diagnosis of urinary tract infection (UTI). Aims: To determine whether parental reporting of smelly urine is of any relevance to the diagnosis of UTI in children less than 6 years of age. Methods: Parents whose children were having urine collected as part of their admission to a large district hospital were given a simple questionnaire to complete regarding the current smell of their child's urine. Parents were asked whether their child's urine smelled different from usual or had a particular smell. Microscopy and culture results of the child's urine were compared to their parent's questionnaire answers to see if there was a association between parental reporting of a different or particular urine smell and a diagnosis of UTI. Results: One hundred and ten questionnaires and urine samples were obtained. Fifty two per cent of parents thought that their child's urine smelled different from usual or had a particular smell. Only 6.4% of children were diagnosed as having a UTI. There was no statistically significant association between parental reporting of abnormal urine smell and diagnosis of UTI. Conclusion: In determining whether a young child has a UTI, asking parents about urine smell is unlikely to be of benefit.